Estimates of Paracetamol Poisoning in Brazil: Analysis of Official Records From 1990s to 2020 - JHH, Okuyama; TF, Galvao; MT, Silva (Frontiers in Pharmacology, 2022)
Objective: To assess the cases of paracetamol poisoning in Brazil. Methods: Analysis of official records of deaths between 1996 and 2019 from the Brazil Mortality Information System (SIM), admissions between 2008 and 2020 from the Hospital Information System (SIH), and cases of poisoning between 2017 and 2020 in health services, reported to the Brazilian Notifiable Diseases Surveillance System (SINAN). In SIM and SIH, records with ICD-10 were included: F55, T39, X40, X60, and Y10. In SINAN, commercial products containing paracetamol were identified. Records were stratified by age, sex, and intentionality. Mean and standard error were calculated for each stratum based on the annual data, by federation unit. Poisoning reports by 1,000,000 inhabitants were calculated from each state and compared to the national average. Results: In total, 492 deaths, 5,666 hospital admissions, and 17,031 cases of paracetamol poisoning were recorded in the period. Deaths occurred mostly among adults (71.3% ± 3.0) and in suicide attempts (37.3% ± 2.7). Hospital admissions were more frequent in adults (69.7% ± 1.4), women (57.1% ± 2.5), and unintentional poisoning (80.2% ± 4.2). Poisoning reports was more also frequent among adults (71.4% ± 1.2), women (74.2% ± 0.6), and due to accidents (79.6% ± 1.8). The South and Southeast regions of the country presented the highest frequencies in all outcomes, above the national average. Conclusion: Paracetamol exposure is a concern for preventable poisonings, hospital admissions and deaths. More accurate data about paracetamol poisoning are required to support surveillance actions and the development of mechanisms to reduce poisoning, particularly related to adults, women and suicide attempts.